PERANCANGAN RUMAH SAKIT IBU DAN ANAK DI KABUPATEN SINTANG - Gunawan, Abdi; Purnomo, Yudi; Andi, Uray Fery (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Health is the most important factor in people's lives, especially the health of mothers and children. The increasing number of births and deaths and the increasing number of residents in Sintang Regency as the 3rd largest Regency in West Kalimantan Province, thus requires a health facility that accommodates services for mothers and children. One type of service is the Mother and Child Hospital (RSIA). The design of this hospital is planned in Sintang District, Sintang Regency. This location was taken based on the issue of the importance of RSIA development, and 2019 Central Statistics Agency (BPS) data which shows that health facilities such as hospitals are not evenly distributed in Sintang Regency in Sintang District. The design method used includes: ideas, data collection, analysis, and the design phase, as well as the results of the design of the maternal and child hospital. This design consists of a linear building that follows the shape of the land. Zoning space is divided and adapts to narrow land forms. Orientation, placement and circulation are regulated based on existing regulations and analysis, so that there is a need for circulation paths as needed, and on the facade of the building it is planned to use several window openings that are used as natural lighting and ventilation in the room.